Pelatihan Penyusunan Laporan Keuangan Dengan Penggunaan Sak Etap Pada Pelaku UMKM Di Padukuhan Sendang - Lorin Eldania Putri; Zaenal Wafa (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2023)
The purpose of recording financial statements for a business is to present fairly the financial position, financial performance and cash flows of the business/business entity. The presentation of business entity financial statements must be presented fairly, in the sense that the presentation is made in an honest manner on the effects of transactions,othereventsand conditions in accordance with the definitions and criteria for recognizing assets, liabilities, capital, income and expenses. therefore the presentation of SAK ETAP plays an important role in the financial management of UMKM in the Padukuhan Sendang village so that it is more organized